Ring Chromosome 13 in an Infant Girl - Jodeiry, B; Rahmani, SA; Javaherizadeh, H; Mirnia, K (Journal of Nepal Paediatric Society, 2014)
Ring chromosome 13, is an uncommon genetic syndrome. We report a girl infant with ring chromosome 13. She is 2nd offspring of family. She had no family history of genetic disorder. Karyotype showed 46xx,r(13). She had hypertelorism, wide nasal bridge, and long philtrum. She is the first report of ring chromosome 13 in Iranian children. DOI: http://dx.doi.org/10.3126/jnps.v34i1.7961 J Nepal Paediatr Soc 2014;34(1):74-76